Attitude Towards Mathematics as Correlate of Achievement in Mathematics - Lalit Kumar; Singh, Priyanka (JOURNAL OF INDIAN EDUCATION, 2011)
Attitude towards mathematics has its bearing on mathematical creativity, achievement in mathematics. Favourable attitude influences achievement, personality, perception and success. In the present study the researchers have tried to establish a relationship between attitude towards mathematics and achievement in mathematics. In the present study 500 higher secondary school students of Patna district have been selected randomly as sample of the study. For the measurement of attitude towards mathematic, the scale developed and standardised by Lalit Kumar has been employed. Achievement of students in maths in their secondary board examination has been taken as their achievement in mathematics. For testing the hypotheses percentage, mean, standard deviation, t-value, coefficient of correlation have been calculated. The study has major findings as — (i) More than 50 per cent higher secondary school students possess favourable attitude towards mathematics, (ii) Attitude towards mathematics is significantly correlated with achievement in mathematics and (iii) Higher group on attitude towards mathematics is significantly superior in their achievement in mathematics in compariosn to lower group on attitude towards mathematics.